Simulation of combustion of sesame and broad bean stalks in the freeboard zone inside a pilot-scale bubbling fluidized bed combustor using CFD modeling. (25th July 2019) - El-Sayed, Saad A.; Noseir, Emad H.
Highlights: A numerical model is used for particle tracking, devolatilization, char oxidation. The predictions are sensitive to the kinetic parameters and other parameters. The numerical model is dependable based on the optimized parameters. The max. abs. deviations for flue gas species and axial temperature are presented. The model simulation results are in a good agreement with the experimental data. Abstract: A two-dimensional numerical model has been developed to simulate combustion of sesame and broad bean stalks in the freeboard zone of a pilot-scale Bubbling Fluidized Bed Combustor (BFBC). Eulerian–Lagrangian approach is used so, the gas phase is treated as a continuum by solving the time-averaged Navier-Stokes equations and a Discrete Phase Model (DPM) is used to model the solid phase. The combustion in the freeboard was simulated to be consistent with the experimental conditions and the real combustor work. Prediction of composition for gas and solid phases at the freeboard inlet was performed. A series of simulations have been performed to examine the effect of chemical kinetic parameters, solid phase parameters, gas phase parameters and heat flux through walls on the numerical results. The model results were validated by comparing with experimental results obtained from the BFBC. The maximum absolute deviations corresponding to the numerical results of the mole fraction of flue gas species at the exit were 3.07% for the sesame stalks and 10.89% for the broad bean stalks. The numerical results of the axial temperature distribution have maximum absolute deviations 14.77% and 14.69% for the sesame stalks and broad bean stalks, respectively. It was found that the model simulation results are in a good agreement with the experimental data obtained from the experiments. In the present model, the deviations of the flue gas species and axial temperature distribution along the freeboard height are found within the literature limits.